Impact of sea water, dead sea water and NaCI on germination, anatomical and antioxidant profile of molokhia (Corchorus olitorius L. Malvaceace) - Taneenah, Ayat Mohammad Mutleq (2017)
High salinity is the most severe environmental stress that effects on seed germination, seedlings, and growth in the life cycle of the plants. Salinity gave negative effect on plant development performance from germination to reproduction such as a reduction in elongation growth, reduction of leaf expansion and reduced stomatal pores and density. Few studies had been done to determine the effect of Sea water and NaCl on the germination, morphology, physiology, and antioxidant activity on Molokhia, and moreover, no study had been on the effect of Dead Sea water on Molokhia plant. This study aimed to understand the response of Molokhia (Corchorus olitorius L.) in different concentration of Dead Sea water, sea water, and NaCl at germination stage., anatomical features and antioxidant activity. Twenty-fivesterilized Molokhia seeds were germinated in sterilized Petri dishes and treated with 5 mldeionized water (control) or with Dead Sea water, sea water, and NaCl (3‰, 6‰, 9‰, 12‰) (part per thousand), with four replicates for each treatment and were arranged randomly. Germination percentage, germination index, germination rate, salt tolerance and seed vigor were calculated. This study found the germination percentage was highest in control, 3 ‰ of Sea water and 3 ‰ of Dead Sea water (98.4 %, 93.9 %, 93.2%) respectivley, howaver, by increasing salinity concentration, seed germination delayed and decreased. Whereas, salt tolerance and seed vigor declined with increasing salinity concentration except at 3 ‰ of Dead Sea water. Biomass, stomatal conductance, and anatomical leaves of Molokhia seedling as germinated in three different types of salt were studied. Twenty seedlings were selected randomly. The results showed that seedling growth characteristics and stomatal conductance significantly reduced (ANOVA, P<0.05) except at 3‰ of Dead Sea water. The highest leaf area was achieved with 3‰ of Dead Sea water (7.60 mm2). This study found that the anatomy of seedlings leaves affected by high concentration of NaCl, sea water, and Dead Sea water (9 to 12) ‰ as salinity concentrations increased, the changes of anatomy and arrangement of cells also increased. Moreover, the arrangement of mesophylls tissues was found in disorder. The amount of chlorophyll a, b, carotenoid, total phenolic content and reduced glutathione were measured spectrophotometrically of Molokhia leaves as responses to Dead Sea water, sea water and NaCl. Around 5gof fullyexpanded leaves were harvested randomly. The concentration of total phenolic compound and carotenoids increased when salinity increased in all treatments which 3‰ of Dead Sea water showed the highest carotenoids (1.10 mg/ml). However, total chlorophyll, chl a and chl b decreased whilst salinity concentration increased except in 3‰ (4.70 mg/ml) and 6 ‰ (4.20 mg/ml) of Dead Sea. Reduced glutathione (GSH) is most important molecules in plant as stress marker, 3‰ and 6‰ of Dead Sea water shows the highest GSH20 μmol/g.FW and 15 μmol/g.FW respectively. The findings of this study revealed that the salt tolerance during germination stage expedient to be used 3‰ of Dead Sea water for germination C.olitorius seed due to increase the biomass of seedling and leaf area exists. Therefore, more study should be conducted on Molokhia plant to understand the ecophysiological strategies for the survival under salinity environment conditions especially under 3‰ of Dead Sea water.